Encyclopædia Britannica : propeadia (Encyclopedia Britannica ; Broderbund, 2000)
Contains the complete text of the Encyclopaedia Britannica (2000 edition) and Merriam-Webster's Collegiate Dictionary. Features over 80,000 articles, more than 8,000 photographs and illustrations, animations, video, sound clips, and links to related Internet resources.